181k views
4 votes
G(x) = 3x - 5 h(x) = 4x - 2 Find (g + h)(8)

User Jennyfer
by
4.6k points

1 Answer

2 votes

Answer:

49

Explanation:

g(x) = 3x - 5

h(x) = 4x - 2

(g + h)(8)

g(8) + h(8)

solve for g(8)

g(x) = 3x - 5

g(8) = 3(8) - 5

g(8)= 24-5

g(8)= 19

solve for h(8)

h(x) = 4x - 2

h(8) = 4(8) - 2

h(8)= 32-2

h(8)=30

plug in

g(8) + h(8)

19+30

49

Hope this helps!

User Courtsimas
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.